Case report: Cryoablation as a novel bridging strategy prior to CAR-T cell therapy for B cell malignancies with bulky disease - Zhang, Xiaomin; Wu, Jinming; Qiao, Liangliang; Chen, Lixuan; Chen, Chaolin; Zhang, Hui; Luo, Rongcheng; Xiao, Yang (Frontiers in Oncology, 2023)
Chimeric antigen receptor (CAR) T-cell therapy has emerged as a powerful immunotherapy in relapsed/refractory (R/R) hematological malignancies, especially in R/R B-cell acute lymphocytic leukemia (B-ALL), non-Hodgkin lymphoma (NHL), and multiple myeloma (MM). To prevent disease progression and reduce tumor burden during CAR-T cell manufacturing, bridging therapies prior to CAR-T cell infusion are crucial. At present, it has been demonstrated that PD-1 blockade, chemotherapies, radiotherapy and autologous stem cell transplantation (ASCT) could serve as effective bridging strategies. However, whether cryoablation could serve as a novel bridging strategy is unknown. In this paper, we report 2 cases of R/R B cell malignancies with bulky disease that were successfully treated with a combination of cryoablation and CAR-T cell therapy. Patient 1 was a 65-year-old female who was diagnosed with R/R MM with extramedullary disease (EMD). She was enrolled in the anti-BCMA CAR-T cell clinical trial. Patient 2 was a 70-year-old man who presented with a subcutaneous mass in the right anterior thigh and was diagnosed with primary cutaneous diffuse large B cell lymphoma, leg type (PCLBCL-LT) 1 year ago. He failed multiline chemotherapies as well as radiotherapy. Thus, he requested anti-CD19 CAR-T cell therapy. Unfortunately, they all experienced local progression during CAR-T cell manufacturing. To rapidly achieve local tumor control and reduce tumor burden, they both received cryoablation as a bridging therapy. Patient 1 achieved a very good partial response (VGPR) 1 month after CAR-T cell infusion, and patient 2 achieved a partial response (PR) 1 month after CAR-T cell infusion. In addition, adverse effects were tolerable and manageable. Our study demonstrated the favorable safety and efficacy of combination therapy with cryoablation and CAR-T cell therapy for the first time, and it also indicates that cryoablation could serve as a novel therapeutic strategy for local tumor control in B cell malignancies.